Brazilian Scale of Hearing and Language Development: Normality Curve for Infants and Children from 0 to 24 Months Old with Normal Hearing - Moretti, Claudia; Ribas, Angela; Guarinello, Ana Cristina; Rosa, Marine; Riesemberg, Renato; Vassoler, Trissia; Sypczuk, Giselle; Martins, Jackeline (International Archives of Otorhinolaryngology, 2019)
Introduction Cochlear implants are currently the most effective technological resource to facilitate access to the hearing world for deaf people. Their use, especially when implanted early in children, reduces the impact of deafness on hearing as well as on the development of spoken language.Objective To validate the first part of the Brazilian Scale of Hearing and Language Development (EDAL-1, in the Portuguese acronym) and to establish the normal curve in infants and children aged between 0 and 24 months old with normal hearing.Method This is an experimental study of a descriptive nature, conducted with 92 infants and children with normal hearing. Every infant/child was evaluated audiologically, and the EDAL-1 was applied to their parents. The responses were categorized by applying the EDAL-1 every 3 months for each child.Results The EDAL-1 was shown to be easily applied by the researcher and easily understood by the parents. It was possible to classify the sample every 3 months and describe the results. The average of the responses found in terms of scores for each age category shows an increasing scale following the evolution of the chronological age: 3 months—34.23 points; 6 months—54.68 points; 9 months—73 points; 12 months—82.5 points; 15 months—87 points; 18 months—91 points; 21 months—92.5 points, and 24 months—95.83 points.Conclusion The normal curve for EDAL-1 was successfully established. The averages can be considered as the standard protocol for normality, serving as a reference for comparison with other populations.
Keywords: hearing; language; clinical protocols; deafness